DIDACTIC DESIGN OF ETHNOMATHEMATICS-BASED MATHEMATICS LEARNING: CONSTRUCTING A VARIETY OF GEOMETRIC ORNAMENTS FROM RIAU BATIK PATTERNS - Armawati; Susilasari; Mhmd Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the integration of local cultural values, especially Riau batik with geometric patterns, into mathematics learning in elementary schools through an ethnomathematics approach. Batik as a cultural heritage not only holds aesthetic value, but also contains mathematical concepts such as symmetry, transformation, and pattern repetition. Using an exploratory qualitative method, researchers analyzed geometric patterns in several typical Riau batik motifs, such as the selembayung, pucuk rebung, and itik balik petang motifs. The results of the study indicate that the integration of ethnomathematics elements from Riau batik can improve students' understanding of geometric concepts, foster appreciation for local culture, and strengthen the relationship between mathematics and real life. This article recommends the development of contextual learning tools based on ethnomathematics as an innovative medium in the implementation of the Merdeka Curriculum in elementary schools.